New versatile Pt supports composed of graphene sheets decorated by Fe2O3 nanorods and N-dopants with high activity based on improved metal/support interactions. Issue 1 (21st November 2014) - Dai, Yunqian; Chai, Yunling; Sun, Yibai; Fu, Wanlin; Wang, Xiaotian; Gu, Qing; Zeng, Tingying Helen; Sun, Yueming
Abstract : Improved catalytic performance was achieved when the well-designed Fe2 O3 /N-RGO sheets served as a new and versatile scaffold for Pt nanocrystals. Abstract : Supported metal catalysts are critical to many important chemical reactions, but the weak metal/support interaction is an obstacle to the success of remarkable catalytic performance. This paper reports rational-designed novel Pt supports, consisting of reduced graphene oxide sheets decorated with both Fe2 O3 nanorods and N-dopants (denoted as Fe2 O3 /N-RGO), for Pt photodeposition driven by visible light in a controllable fashion. The 2–3 nm Pt nanocrystals primarily nucleated on rough Fe2 O3 nanorods, and interacted strongly with special sites on the Fe2 O3 surface using unsaturated vacant orbitals. At the same time, the accelerated photodegradation of undesirable PVP allowed the Pt nanocrystals with clean active sites. The supported Pt showed impressive activity and had a 7-times higher reaction rate constant (11.4 s −1 mg −1 ) towards 4-nitrophenol reduction, compared with that of free Pt, due to the synergetic effect within the whole Pt/Fe2 O3 /N-RGO catalysts and the doping of N atoms which acted as new metal-free catalytic centers in N-RGO sheets. We further demonstrated that the ternary catalyst could be easily removed through magnetic separation from the system. This new strategy is extendible to other heterogeneous catalysts with different components.